Structural Characterization and Functional Properties of Flaxseed Hydrocolloids and Their Application - Lorenc, František; Jarošová, Markéta; Bedrníček, Jan; Smetana, Pavel; Bárta, Jan (Foods (Basel, Switzerland), 2022)
Flaxseed is an excellent source of valuable nutrients and is also considered a functional food. There are two types of hydrocolloids in flaxseed: flaxseed gum and proteins. Flaxseed gum exhibits emulsifying and foaming activities or can be used as a thickening and gelling agent. Due to its form of soluble fiber, flaxseed gum is related to many health benefits. Flaxseed proteins have various functional properties based on their physicochemical properties. While albumins possess the emulsion-forming ability, globulins better serve as foaming agents. Flaxseed proteins may also serve as a source of functional peptides with interesting biological and health-related activities. Functional properties and health-related benefits predetermine the application of these hydrocolloids, mainly in the food industry or medicine. Although these properties of flaxseed hydrocolloids have been recently and extensively studied, they are still not widely used on the industrial scale compared to other popular plant gums and proteins. The aim of this review was to present, discuss and highlight the recent discoveries in the structural characteristics and functional and biological properties of these versatile hydrocolloids with respect to factors affecting their characteristics and offer new insights into their potential applications as comparable alternatives to the other natural hydrocolloids or as the sources of novel functional products.
Keywords: health benefits; flaxseed proteins; flaxseed gum; functional properties; flaxseed; food hydrocolloids; Linum usitatissimum L.